FAULT DETECTION IN ROTATING MACHINERY BY USING THE MODAL STATE OBSERVER APPROACH - Leao, Leandro de S.; Cavalini, Aldemir Ap.; Morais, Tobias S.; Melo, Gilberto Pechoto de [UNESP]; Steffen, Valder; ASME (Amer Soc Mechanical Engineers, 2017)
The presence of transversal cracks in rotating shafts can lead to catastrophic failures, which imply economic losses and security issues. In the last years, an important attention has been devoted to this subject, leading to the development of several vibration-based structural health monitoring approaches. In this paper, a fault detection technique based on the so-called modal state observer is applied to detect transversal cracks in rotating machines. The Luenberger state observer is described in modal domain to determine the most affected vibration modes due to the crack presence. A cracked rotor composed by a flexible horizontal shaft, two rigid discs, and two self-aligning ball bearings is used for illustration purposes. The additional flexibility introduced by the crack is calculated by using the linear fracture mechanics theory. The breathing behavior of the crack is simulated according to the Mayes' model, in which the crack transition from fully open to fully closed is described by a cosine function. The obtained results lead to the conclusion that the modal state observer is a potential technique to detect cracks in rotating machines.